The Cambridge encyclopedia of human evolution - Jones, Steve, 1944-; Martin, R. D., (Robert D.), 1942-; Pilbeam, David R. (New York : Cambridge University Press, 1992)
Introduction to human evolution with coverage ranging from genetics to demography and disease. Includes diagrams, maps, and photographs.
Patterns of primate evolution -- The life of primates -- The brain and language -- Primate social organisation -- Human evolution in a geological context -- The primate fossil record -- Primate genetics and evolution -- Genetic clues of relatedness -- Early human behaviour and ecology.
"First published in 1992, reprinted in 1994"--Verso t.p.
Includes bibliographical references (p. 473-486) and index.
Library Journal Starred.
Wilson's Public Library.
Wilson's Senior High School.
Young Adult
Keywords: Human evolution -- Encyclopedias; Evolution -- Dictionaries